AN ANALYSIS OF THE ENGLISH TEXTBOOK “HELLO JAKARTA GRADE V” FOR ELEMENTARY STUDENTS - Gracia Octora; Iwan Ridwan; Kelik Wachyudi (IKIP Siliwangi, 2023)
Learning English in elementary schools, it is essential to use textbooks suitable for students because textbooks can support the teaching and learning process in a class by studying the material. Textbooks are ideal for students and can be adapted to Permendikbud No. 8 of the 2016 framework concerning National Education Book Standards used by Education Units. This study aims to describe and analyze the feasibility of an English textbook for grade 5 elementary schools entitled